Career opportunities in library and information science - Taylor, T. Allan (Ferguson, 2009)
Whether you're a student or a professionals ready for a career change, you'll find in this invaluable book everything you need to know to start an exciting career or alter the direction of your current career in library and/or information science. Features include a quick-reference Career Profile for each job summarizing its notable features, a Career Ladder illustrating frequent routes to and from the position described, and a comprehensive text pointing out special skills, education, training, and various associations relevant to each post. Appendixes list educational institutions, periodicals and directories, professional associations, and useful industry Web sites.